Bodily experiences, body image and social identity of persons with blindness: a qualitative study in Greece - Κούτρα Λίνα; Τόγκας Κωνσταντίνος; Αλεξιάς Γεώργιος; Σαββάκης Μάνος; Στρατοπούλου Ιφιγένεια (The Greek Review of Social Research, 2018)
Although blindness is a frequent type of disability, bodily experiences, body image and social identity of the blind persons have not been extensively investigated. A qualitative study was conducted using interviews of seven blind people and the results showed that their sense of identity is strongly structured, without stigma and without problems in their socialization. Blind individuals don’t accept the concept that they are different from the other people and rely on their senses only for their daily survival. Bodily experiences are essential to the recognition of their environment, and outward appearance is a basic element of their self image. Visually impaired people do not have any uncertainty and dissatisfaction for their bodies and have no problems developing and maintaining a positive body image. The results can be used for their integrated psychosocial care.